Safety and immunogenicity of an adjuvanted protein therapeutic HIV-1 vaccine in subjects with HIV-1 infection: a randomised placebo-controlled study - Harrer, Thomas; Plettenberg, Andreas; Arasteh, Keikawus; Van Lunzen, Jan; Faetkenheuer, Gerd; Jaeger, Hans; Janssens, Michel; Burny, Wivine; Collard, Alix; Roman, Francois; Loeliger, Alfred; Koutsoukos, Marguerite; et al. (Vaccine, 2014)
The human immunodeficiency virus type-1 (HIV-1) vaccine candidate F4/AS01 has previously been shown to induce potent and persistent polyfunctional CD4(+) T-cell responses in HIV-1-seronegative volunteers. This placebo-controlled study evaluated two doses of F4/AS01 1-month apart in antiretroviral treatment (ART)-experienced and ART-naïve HIV-1-infected subjects (1:1 randomisation in each cohort). Safety, HIV-1-specific CD4(+) and CD8(+) T-cell responses, absolute CD4(+) T-cell counts and HIV-1 viral load were monitored for 12 months post-vaccination. Reactogenicity was clinically acceptable and no vaccine-related serious adverse events were reported. The frequency of HIV-1-specific CD4(+) T-cells 2 weeks post-dose 2 was significantly higher in the vaccine group than in the placebo group in both cohorts (p<0.05). Vaccine-induced HIV-1-specific CD4(+) T-cells exhibited a polyfunctional phenotype, expressing at least CD40L and IL-2. No increase in HIV-1-specific CD8(+) T-cells or change in CD8(+) T-cell activation marker expression profile was detected. Absolute CD4(+) T-cell counts were variable over time in both cohorts. Viral load remained suppressed in ART-experienced subjects. In ART-naïve subjects, a transient reduction in viral load from baseline was observed 2 weeks after the second F4/AS01 dose, which was concurrent with a higher frequency of HIV-1-specific CD4(+) T-cells expressing at least IL-2 in this cohort. In conclusion, F4/AS01 showed a clinically acceptable reactogenicity and safety profile, and induced polyfunctional HIV-1-specific CD4(+) T-cell responses in ART-experienced and ART-naïve subjects. These findings support further clinical investigation of F4/AS01 as a potential HIV-1 vaccine for therapeutic use in individuals with HIV-1 infection.
EVALuna2:12915